Prognostic factors associated with 15-year mortality in patients with hospitalized systolic HF: Results of the observational community-based EPICAL cohort study. (1st February 2017) - Agrinier, Nelly; Thilly, Nathalie; Briançon, Serge; Juillière, Yves; Mertes, Paul-Michel; Villemot, Jean-Pierre; Alla, François; Zannad, Faiez; ,
Abstract: Aims: Little data on very long-term survival and associated prognostic factors in heart failure (HF) are available. The aim was to describe 15-year survival and to identify the baseline prognostic factors associated with mortality in a community-based sample of patients hospitalized for systolic HF. Methods: Vital status was collected 15 years after inclusion of 352 patients hospitalized for systolic HF born in France from the prospective cohort EPICAL. The prognostic value of baseline socioeconomic, clinical and biological characteristics on 15-year mortality was assessed using Cox models. Results: The mean (± SD) age was 63.9 (± 10.8) years, 76% of the patients were male, median left ventricular ejection fraction (LVEF) was 23% IR [18–27]. Overall, the mean (± SD) follow-up was 1826 (± 111) days. A total of 290 (82.4%) deaths and 22 heart transplantations occurred during the follow-up. The 15-year survival rate was 13.2% (95% CI [9.0–16.3]), i.e. 4.7 times lower than the one observed in the general population. Baseline characteristics associated with 15-year mortality were: age older than 65 years (HR = 1.48, CI 95% [1.15–1.90]), diabetes mellitus (1.31 [1.00–1.72]), chronic kidney disease (1.73 [1.23–2.43]), serious comorbidity (1.29 [1.02–1.64]), time from first HF diagnosis exceeding 1 year at inclusion (1.68 [1.26–2.24]), HF hospitalization during the previous 12 months (1.36 [1.04–1.78]), heart rate higher than 110 beats per minute (1.87 [1.26–2.76]), LVEF % (0.88 per quartile increase [0.80–1.98]), and serum sodium below 130 mmol/L (3.14 [1.76–5.61]. Conclusions: Only 13% of patients hospitalized for HF survived at 15 years. The usual mid-term prognostic factors are also predictive of very long-term survival.